مشروعية نكاح المتعة عند الإمامية الإثنى عشرية وموقف المذاهب الإسلامية منها - Fithriah Wardi (Universiti Sains Islam Malaysia, 2024)
Both fuqaha (Moslem jurists) of the Sunni and the Shi’ah are in agreement that Mut’ah marriage was permitted at the beginning of Islam, based on Al-quran verses and Rasulullah (pbuh) hadiths. However, they disagree as to the annulment and permissibility. The Shi’as considered Mut’ah marriage as permitted until the Day of Resurrection, meanwhile the Sunni viewed it as forbidden. The execution of Mut’ah marriage has always been singled out as one of the specific features of the Shi’ite doctrine in which denying it means denial of the religion. They also believe that woman who practised Mut’ah marriage will result in her sins being forgiven. According to the Shi’ites, Mut’ah marriage is one of the biggest reasons for someone to be granted heaven, and his status be elevated to the rank of the Holy Prophet PBUH. Hence, it can be said that practicing Mut’ah marriage is one of the most crucial issues among the Shi’ite community which is totally contradicted to the Sunni doctrine which believed it is unlawful marriage and equalized to Zina (adultery). There is no doubt that this is one of the most important topics that lead to the dispute between the two schools of thought. Using the descriptive and analytical methods, this study aims to elaborate the views on the issue from Shi’ite and Sunni points of view based on various proofs (adillah) and their argumentations in supporting the views.